Cells susceptible to epithelial-mesenchymal transition are enriched in stem-like side population cells from prostate cancer - LUO, YONG; CUI, XINHAO; ZHAO, JIAHUI; HAN, YILI; LI, MINGCHUAN; LIN, YUNHUA; JIANG, YONGGUANG; LAN, LING (Oncology reports, 2014)
Accumulating evidence suggests that epithelial-mesenchymal transition (EMT) acts as an important factor for the promotion of tumor progression. Strategies for suppressing EMT remain the subject of ongoing research. In the present study, fluorescence-activated cell sorting (FACS) was used to isolate side population (SP) cells from human prostate cancer (PCa) cell lines and xenograft tissues. After identifying their molecular and functional stem-like characteristics, stem-like SP cells from a cell line and from xenograft tissue were transfected with hypoxia inducible factor-1α (HIF-1α). The potential of the prostate stem-like SP cells to undergo EMT was compared with that in their bulk counterparts after HIF-1α introduction. Stem-like SP cells acquired more complete EMT molecular features and exhibited stronger aggressive capability than the homologous bulk population cells both in vitro (proliferation and invasion) and in vivo (tumorigenesis and metastasis formation). We, therefore, concluded that EMT is closely associated with tumor heterogeneity, and that PCa cells susceptible to EMT are enriched in stem-like SP cells. These findings disclose a new approach, targeting the cellular basis of the EMT process that may help to identify effective and accurate methods for suppressing tumor growth and preventing distant dissemination.